Regional Practice of Project Management in the Process of Primary Health Care Improvement by using Supply Chain Strategy - Nataliya N Zubareva; Oleg N. Polukhin (International Journal of Supply Chain Management, 2019)
Abstract- The article reveals the practice of project approach application in the process of primary health care system improvement by using the supply chain strategy. A special place is given to the description of the project â€œHealth Managementâ€ implementation process, initiated in the Belgorod Region. They provided the characteristic of the project stages and its intermediate effects. They presented the experience of project activities by conditional blocks. The main results of the regional project are shown. Ideology and project activities are aimed at strategic goal achievement - the provision of life expectancy up to 75 years, including healthy one, among the regional population by 2020.